α-Conotoxin TxIB Reversed Nicotine-Induced Locomotor Sensitization and Nicotine-Enhanced Dopaminergic Activity in Mice - Weifeng Xu; Meiting Wang; Xiaodan Li; Rongyan He; Ren-Bo Ding; Jiaolin Bao; Dongting Zhangsun; Sulan Luo (Marine Drugs)
Nicotine addiction is a serious global public health problem, so there is an urgent necessity to develop novel effective smoking cessation treatments with fewer adverse effects. Spontaneous behavioral sensitization induced by repeated intermittent exposure to the addictive substance represents a classical animal model of addiction research. A significant contributor to nicotine addiction is its interaction with α6β2* nAChRs located on midbrain dopaminergic neurons, which leads to an increase in dopamine (DA) release. α-Conotoxin (α-CTx) TxIB is a novel potent antagonist of the α6/α3β2β3* nAChRs, with an IC50 value of 28.4 nM developed by our group. In this study, we aimed to investigate the effectiveness of α-CTx TxIB in countering nicotine-induced behavioral sensitization and moderating the impact of nicotine on dopamine accumulation in the midbrain. Our results demonstrated that repeated nicotine administration remarkably elevated the locomotor activity of mice, including the number of entries, average speed, and total distance traveled, which could be effectively attenuated by α-CTx TxIB intervention in a dose-dependent manner (1 nmol and 5 nmol TxIB per mouse). Furthermore, 5 nmol α-CTx TxIB significantly reduced the nicotine-elevated DA and norepinephrine (NE) levels in the ventral tegmental area (VTA) and nucleus accumbens (NAc) of mice. 5 nmol α-CTx TxIB also markedly decreased the expression of critical proteins such as the dopamine transporter (DAT), N-methyl-D-aspartic acid receptor (NMDAR), and c-Fos in the NAc and prefrontal cortex (PFC) of the nicotine-exposed mice. This research provided the first compelling evidence that α-CTx TxIB attenuated nicotine-induced locomotor sensitization and inhibited the nicotine-induced dopamine elevation in mice. These results open up new avenues for exploring the therapeutic potential of α-CTx TxIB in the treatment of nicotine addiction.